Three-dimensional embroidered current collectors for ultra-thick electrodes in batteries. Issue 74 (22nd July 2016) - Aguiló-Aguayo, N.; Espiñeira, P. Pena; Manian, A. P.; Bechtold, T.
Abstract : Picture (left) and photomicrograph (right) of the embroidered LiFePO4 cathode. The discharge reaction on the electrode surface is also illustrated. Abstract : A major bottleneck in batteries arises from the limitations in charge transfer between the active mass and the current collector. A number of strategies to increase the surface of current collectors have been proposed, examples are foam electrodes, porous nano-structured surfaces, coatings with carbon nanotubes. A simple and cost efficient approach to increase the surface of current collectors, which utilizes three-dimensional embroidered metal structures, is presented in this paper. In particular, for ultra-thick electrodes benefits with regard to mass loading and impedance could improve overall performance. In this paper we compare the electrochemical performance of thick LiFePO4 cathodes prepared with 3D embroidered aluminium current collectors versus aluminium planar foils, over a range of mass loadings. The 3D cathodes exhibit lower impedances, higher specific capacities, and higher energy efficiencies (up to 8% gain) as compared to the planar cathodes. The 3D cathodes also exhibit greater mechanical stability. These results, which demonstrate the potential for the use of 3D embroidered current collectors in preparation of high-energy batteries, can also be extended to other chemistries.